A New Approach for Developing Spectrophotometric Determination of Phenylephrine Drug in Pure, Pharmaceutics and Serum Samples Using Sodium Periodate as Oxidizing Agent via a Green Method of CFIA/Merging Zone Technique - Shahad L. Hamed; Bushra B. Qassim (مجلة بغداد للعلوم, 2024)
The research involved a rapid, automated and highly accurate developed CFIA/MZ technique for estimation of phenylephrine hydrochloride (PHE) in pure, dosage forms and biological sample. This method is based on oxidative coupling reaction of 2,4-dinitrophenylhydrazine (DNPH) with PHE in existence of sodium periodate as oxidizing agent in alkaline medium to form a red colored product at ʎmax )520 nm (. A flow rate of 4.3 mL.min-1 using distilled water as a carrier, the method of FIA proved to be as a sensitive and economic analytical tool for estimation of PHE.